Exact Performance of CoD Estimators in Discrete Prediction. (27th July 2010) - Chen Chen, Ting Ting; Braga-Neto Braga-Neto, Ulisses Ulisses
Abstract : The coefficient of determination (CoD) has significant applications in genomics, for example, in the inference of gene regulatory networks. We study several CoD estimators, based upon the resubstitution, leave-one-out, cross-validation, and bootstrap error estimators. We present an exact formulation of performance metrics for the resubstitution and leave-one-out CoD estimators, assuming the discrete histogram rule. Numerical experiments are carried out using a parametric Zipf model, where we compute exact performance metrics of resubstitution and leave-one-out CoD estimators using the previously derived equations, for varying actual CoD, sample size, and bin size. These results are compared to approximate performance metrics of 10-repeated 2-fold cross-validation and 0.632 bootstrap CoD estimators, computed via Monte Carlo sampling. The numerical results lead to a perhaps surprising conclusion: under the Zipf model under consideration, and for moderate and large values of the actual CoD, the resubstitution CoD estimator is the least biased and least variable among all CoD estimators, especially at small number of predictors. We also observed that the leave-one-out and cross-validation CoD estimators tend to perform the worst, whereas the performance of the bootstrap CoD estimator is intermediary, despite its high computational complexity.